6 Knowledge on occupational hazards and associated socio demographic factors among nurses at Teaching Hospital Jaffna - Seruba, G.; Perera, W.D.W.; Thabotharan, D.; Kamalarupan, L. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
Nurses are the front line of risks and victims of occupational hazards among healthcare professionals. These hazards may affect the well-being of the nurses. A thorough understanding of occupational hazards helps promote a safer workplace among nurses. Objectives: This study assesses the knowledge of occupational hazards and associated socio-demographic factors among nurses at Teaching Hospital Jaffna. Methodology: This hospital-based cross-sectional study was carried out among 370 nurses at Teaching Hospital Jaffna. Ethical clearance was obtained from the Ethical Review Committee, Faculty of Medicine, University of Jaffna. A stratified random sampling method was used to select samples based on the population proportion of the nurses in wards/units/clinics. A pre-tested and validated self-administered questionnaire was used to collect the data regarding five types of occupational hazards. The data were analyzed, and the Pearson chi-square test was used to find the association between the level of knowledge and socio-demographic factors by using IBM SPSS 20. Results: The response rate was 90.24%. The age range of the participants was 25-46 years. The mean age of the participants was 31.65 (SD±4.943) years. More than half of them were single (67.3%). Three-fourths of the participants completed a diploma in nursing (75.4%); meanwhile, 24.3% of them got BSc in nursing. The majority had working experience of less than five years (61.6%). Nearly half of them are working in units (51.1%). Around 84.3% of them had good knowledge, respectively moderate and poor knowledge percentages were 14.3% and 1.4%. The mean score for the knowledge was 18.24 (SD ±2.952) out of a total score of 20. Age (0.001), working experience (0.031), marital status (0.009), and educational qualification (0.044) showed a statistically significant association with the level of knowledge regarding occupational hazards. Conclusion: Even though, majority of them have a good knowledge level, providing an in-service training program regarding occupational hazards can improve the knowledge level further.
Keywords: Hospital,; Occupational hazards; Nurses; Knowledge; Jaffna